The road to astaxanthin production in tomato fruit reveals plastid and metabolic adaptation resulting in an unintended high lycopene genotype with delayed over‐ripening properties. Issue 8 (1st February 2019) - Enfissi, Eugenia M.A.; Nogueira, Marilise; D'Ambrosio, Caterina; Stigliani, Adriana Lucia; Giorio, Giovanni; Misawa, Norihiko; Fraser, Paul D.
Summary: Tomato fruit are an important nutritional component of the human diet and offer potential to act as a cell factory for speciality chemicals, which are often produced by chemical synthesis. In the present study our goal was to produce competitive levels of the high value ketocarotenoid, astaxanthin, in tomato fruit. The initial stage in this process was achieved by expressing the 4, 4′ carotenoid oxygenase ( crtW ) and 3, 3′ hydroxylase ( crtZ ) from marine bacteria in tomato under constitutive control. Characterization of this genotype showed a surprising low level production of ketocarotenoids in ripe fruit but over production of lycopene (~3.5 mg/g DW), accompanied by delayed ripening. In order to accumulate these non‐endogenous carotenoids, metabolite induced plastid differentiation was evident as well as esterification. Metabolomic and pathway based transcription studies corroborated the delayed onset of ripening. The data also revealed the importance of determining pheno/chemotype inheritance, with ketocarotenoid producing progeny displaying loss of vigour in the homozygous state but stability and robustness in the hemizygous state. To iteratively build on these data and optimize ketocarotenoid production in this genotype, a lycopene β‐cyclase was incorporated to avoid precursor limitations and a more efficient hydroxylase was introduced. These combinations resulted in the production of astaxanthin (and ketocarotenoid esters) in ripe fruit at ~3 mg/g DW. Based on previous studies, this level of product formation represents an economic competitive value in a Generally Regarded As Safe (GRAS) matrix that requires minimal downstream processing.